(untitled) (Journal of Transport System Engineering, 2023)
The formation of the primary vortex above the wing is dependent on the Reynolds number, the angle of attack, the Mach number, and the bluntness of the leading edge. This experiment is done in order to assess the impacts of blowing at three sites on the delta wing’s flow topology. The blower was placed on the leading edge at the 15%, 50%, and 70% wing sections. The experiment was conducted at a Reynolds number of 8 x 105, which corresponds to a wind speed of 25 m/s and a mean aerodynamic chord. The UTM generic delta wing model with a 55° sweep angle was employed, and the experiment was conducted at the Low-Speed Wind Tunnel at UniversitiTeknologi Malaysia (UTM-LST). During each experiment, the model was subjected to surface pressure monitoring techniques. This project’s findings show the influence of blowing on the flow topology above the wing.In specific test settings, the installation of the blower at positions 50 percent significantly increased the size of the primary vortex while delaying its breakdown at greater angles of attack.